Paco Ignacio Taibo II - Álvarez Tovar, Adriana; González Cabello, Jaime; Gutiérrez, Myrna Guadalupe (Actas Revista de Historia de la Universidad Autónoma de Nuevo Léon, 2022)
"Se ha ido enfriando la relación de los ciudadanos con su pasado"